Análisis descriptivo del estado de salud de los adultos mayores de la Pontificia Universidad Católica del Ecuador, Ibarra - Biñachig Ipiales, Melany Scarleth (2024)
Health statistics worldwide and in Ecuador on chronic-degenerative diseases indicate that they are constantly increasing and that these, in turn, are a product of the population increase of older adults (PAM) with deteriorating health. In this sense, to detect in time the risks of suffering from these diseases that generate dependency and lead to dysfunctionality in this age group, it was decided to carry out an investigation whose objective was to describe the health status of older adults through measurement. of the four spheres of Comprehensive Geriatric Assessment in the Community of workers and retirees of the PUCE Ibarra, during the period January 2024. For this, a descriptive, cross-sectional and non-experimental study was carried out, taking as a sample 30 adults over 60 years of age. Among the results obtained, it stands out that 50% of the population is overweight, 43% had high blood pressure and 7% had diabetes mellitus\; On the other hand, 43% of the population has signs of sarcopenia and there is a tendency for 13 % of the population is at risk of presenting dementia and depression. These results indicate the need to design and implement programs related to the practice of healthy habits to maintain the health, functionality and independence of this long-lived population.